The method of calculating power supply for monitoring and metering devices of DC traction network based on serial chain of voltage converters - Yu. V. Plotnikov (Омский научный вестник)
For organization of power supply of devices for monitoring and accounting of electric energy for railway traction networks of direct current, the topology of the power source based on a serial chain of voltage converters can be used. The paper considers the development of a methodology for the electrical calculation of such sources. For this purpose, lists of initial data and calculation results are formed. A substitution scheme of ideal elements is proposed. The operation of the substitution scheme is analyzed using the «equivalent source» method. It also provides formulas and recommendations for selecting and determining the required parameters. The adequacy of the proposed method is confirmed by a full-scale experiment.